An Econometric Analysis of the Relationship Between the Namibian Government Debt and Economic Growth - Shipila, Ndeshihafela Melao (Graduate School of Business (GSB), 2019)
The association between government debt and economic growth is complex. Namibia is not excluded from this spectacle as concerns are mounting about the fast-increasing state debt and its implication on economic growth in the long run. By the end of 2016, government debt constituted 40.6 percent of Gross Domestic Product (GDP). Domestic and external debt constituted 25.3 and 15.3 percent of GDP respectively. Total interest paid on state debt stood at about 1 percent of GDP. Various financial debates stress that the debt incurred to enhance economic growth via investment should also consider interest payment costs. Counterarguments emphasise that if governments borrow to stimulate growth via increased economic earnings, then state debt growth might not pose a problem to the economy. This study examined the relationship between economic growth and government debt components for Namibia over the sample period 2000-2016. The study employed a time series econometric model method to examine the nature of the relationship that exists between government debt indicators and economic growth. The augmented Dickey-Fuller (ADF) was employed in testing the unit root characteristics of the series and to determine the order of integration. The autoregressive distributed lag (ARDL) cointegration framework was also employed to determine whether there is a long run and short-run relationship between the variables. Finally, the Granger Causality Test was conducted to test causation between the variables. To investigate these issues, quarterly time series data for the period 2000-2016 was used. The results of cointegration analysis supports the existence of a positive long run cointegration relationship between government debt indicators and economic growth to indicate that debt drives economic growth in Namibia. The study found no causality effect between general debt, foreign debt, domestic debt and GDP. The main policy recommendation from this study is that, in order to avoid the country from plunging into a debt crisis, the Namibian government should consider determining an optimal debt-to-GDP ratio to serve as an indicator beyond which an increase in debt will be deemed unsustainable. The government should further ensure that the debt Fund is used for production and infrastructure development instead of consumption spending to stimulate the productive capacity of the economy.